Online monitoring of dissolved oxygen tension in microtiter plates based on infrared fluorescent oxygen-sensitive nanoparticles. Issue 1 (December 2015) - Ladner, Tobias; Flitsch, David; Schlepütz, Tino; Büchs, Jochen
Abstract Background During the past years, new high-throughput screening systems with capabilities of online monitoring turned out to be powerful tools for the characterization of microbial cell cultures. These systems are often easy to use, offer economic advantages compared to larger systems and allow to determine many important process parameters within short time. Fluorescent protein tags tremendously simplified the tracking and observation of cellular activity in vivo. Unfortunately, interferences between established fluorescence based dissolved oxygen tension (DOT) measurement techniques and fluorescence-based protein tags appeared. Therefore, the applicability of new oxygen-sensitive nanoparticles operated within the more suitable infrared wavelength region are introduced and validated for DOT measurement. Results The biocompatibility of the used dispersed oxygen-sensitive nanoparticles was proven via RAMOS cultivations forHansenula polymorpha, Gluconobacter oxydans, andEscherichia coli . The applicability of the introduced DOT measurement technique for online monitoring of cultivations was demonstrated and successfully validated. The nanoparticles showed no disturbing effect on the online measurement of the fluorescence intensities of the proteins GFP, mCherry and YFP measured by a BioLector prototype. Additionally, the DOT measurement was not influenced by changing concentrations of these proteins. The kL a values for the applied cultivation conditions were successfully determined based on the measured DOT. Conclusions The introduced technique appeared to be practically as well as economically advantageous for DOT online measuring in microtiter plates. The disadvantage of limited availability of microtiter plates with immobilized sensor spots (optodes) does not apply for this introduced technique. Due to the infrared wavelength range, used for the DOT measurement, no interferences with biogenic fluorescence or with expressed fluorescent proteins (e.g. YFP, GFP or mCherry) occur.